Wetland Governance: Contested Aspirations and Reflexive Roles of Local Professionals Toward Worlding Cities in Tai Lake Basin - Wang, Ting (Frontiers in Environmental Science, 2020)
This paper examines the contested agendas generated by Tai Lake Basin’s recent wetland constructions and how these dynamics have stimulated the particular aspirations concerning nature among various local actors. Through interviews with local ecologists, landscape architects, and environmental engineers, this paper details how they convergently subscribe to the ethical claims of humans and nature during the decision making in constructing wetlands, which I have termed as ‘Ecological Governmentality’. Under the influence of environmental conservation as a global consensus, the idea of ‘wetland’ has regained prevalence among Chinese cities’ plans and policies in recent decades. In the Tai Lake Basin, one of the most developed regions in southeast China, over 800 ‘wetland parks’ have been established. Situated in the basin context, this paper further problematizes three modalities of wetland construction in the case of Suzhou city, namely: National Certificated Wetland Parks propelled by international environmental conservation agendas, Urban Wetland Landscape Parks associated with urban redevelopment, and Engineering Constructed Wetlands generated by the opening niche market for municipal water works. The construction of these parks has made prominent attempts to rewild the urban environment through re-territorialization, design, and technology innovations intersected with moral claims that go beyond pure scientific concerns of ecology. Building on the concept of ‘worlding practices’ and ‘governmentality’, three cases in this paper illustrate how the mainstreaming of wetlands in Suzhou has been materialized along with the shared notion of city branding from global neoliberal urbanization. More specifically, this paper explores the diverse materialization through the lens of contested ethical aspirations and transferred roles taken by different actors in the local wetland governance. The emerging ‘Ecological Governmentality’ in wetland construction helps to consolidate the unique ecological imaginary in China and diversify the Chinese cities’ globalization in the making.